2019
DOI: 10.1016/j.bja.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sub-perineural injection using a targeted intracluster supraclavicular ultrasound-guided approach in cadavers

Abstract: Background: Multi-injection targeted intracluster injection ultrasound-guided supraclavicular brachial plexus block has been advocated to provide a faster onset of anaesthesia compared with a double injection technique. By placing the needle within clusters of hypoechoic structures, corresponding to neural tissue, this technique may increase needle trauma and the incidence of nerve injury. This study assessed the rate of sub-perineural needle placement with a single intracluster brachial plexus injection in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
18
0
1
Order By: Relevance
“…From this current study, we can confirm that the prevailing ideas around intrafascicular and extrafascicular injection13 14 as a consequence of deliberate or accidental intraneural injection are most probably incorrect. This follows our paper4 that clearly demonstrated that injection into the endoneurium of a fascicle is highly unlikely to impossible.…”
Section: Discussionsupporting
confidence: 75%
“…From this current study, we can confirm that the prevailing ideas around intrafascicular and extrafascicular injection13 14 as a consequence of deliberate or accidental intraneural injection are most probably incorrect. This follows our paper4 that clearly demonstrated that injection into the endoneurium of a fascicle is highly unlikely to impossible.…”
Section: Discussionsupporting
confidence: 75%
“…Chances of drug being injected within the perineurium during sub-epineural injections are being highlighted in recent cadaver studies. [ 25 26 ] Hence, a novice anaesthesiologist should develop adequate needling skills before contemplating on sub-epineural injections and executing needle choices.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the safety of needletip placement inside the neural clusters is controversial. Most studies seem to support the safety and effectiveness of subfascial injection technique [23][24][25]15], however a recent cadaver study reported that a single ultrasound-guided intracluster injection could lead to a high risk of sub-perineural injections (24%) in the supraclavicular fossa [26]. A stimulating current of 0.4 mA was commonly used to avoid intraneural injection and we did discontinue needle advance and LA injection in the presence of pain or high injection resistance in the present study.…”
Section: Discussionmentioning
confidence: 78%